Synergistic deficits in parvalbumin interneurons and dopamine signaling drive ACC dysfunction in chronic pain - Kevin Lançon; Jiakang Tian; Haleigh Bach; Pierre Drapeau; Jean-Francois Poulin; Philippe Séguéla (Proceedings of the National Academy of Sciences, 2025)
Chronic pain arises from maladaptive changes in both peripheral and central nervous systems, including the anterior cingulate cortex (ACC), a key region implicated in descending pain modulation. Chronic pain increases the excitability of pyramidal neurons in the ACC. Although a reduction in inhibitory inputs onto pyramidal neurons has been observed in neuropathic conditions, the identity of the specific interneurons responsible remains unclear. We show that chronic pain selectively impairs parvalbumin (PV), but not somatostatin, interneurons in the rostral ACC. This is characterized by a decrease in the density of PV interneuron processes, a reduction in their surrounding perineuronal net, and a lower expression of PV. Functionally, PV interneurons display diminished inhibitory efficacy in vitro and reduced phasic activation in response to aversive stimuli in vivo. Dopamine (DA) fibers preferentially contact PV interneurons and excite them via D1 dopamine receptor activation, increasing their excitability and enhancing the frequency of inhibitory postsynaptic currents on pyramidal neurons in healthy, but not neuropathic, conditions. Furthermore, we show that this pathway is involved in hunger-induced analgesia: Food deprivation increases DA release in the ACC and consequently decreases pain thresholds in neuropathic mice. Conversely, when mice are not food deprived, neuropathic pain significantly reduces DA release in the ACC. We conclude that the loss of PV interneuron inhibitory efficacy, alongside convergent hypodopaminergic signaling, synergistically contributes to pathological ACC dysfunction and associated symptoms of chronic pain.